Assessment of the microbiological quality of popular food items on sale in secondary school canteens of Mauritius - Goburdhun, Dayawatee (Ital J Food Saf, 2019)
This study was carried out to assess the microbiological status of three hot meals served in eight selected school canteens of Mauritius, with two schools randomly selected from each of the four school zones of the island. Three individual samples of farata, panini, or fried noodles were collected at each school during two independent visits. The three individual samples of each food type collected during each visit were then pooled before being subjected to microbiological analyses. A total of 48 composite samples were analyzed. The parameters tested were Total Viable Count (TVC), Escherichia coli, Salmonella spp., Clostridium perfringens, Staphylococcus aureus, and Listeria spp. The microbiological analyses revealed that paninis were deemed as generally acceptable with TVC falling in the range of 3.0-5.7 Log CFU/g and undetectable levels of S. aureus and E. coli. In contrast, fried noodles and faratas harboured a moderately high level of TVC (4.4-6.7 Log CFU/g) and objectionably high levels S. aureus (3.1 to 5.0 Log CFU/g) and E. coli (3.1-5.1 Log CFU/g) for seven out of the eight schools.